2022
DOI: 10.1155/2022/1930185
|View full text |Cite
|
Sign up to set email alerts
|

KDELR3 Is a Prognostic Biomarker Related to the Immune Infiltration and Chemoresistance of Anticancer Drugs in Uveal Melanoma

Abstract: Uveal melanoma (UM) is an intraocular malignancy in adults in which approximately 50% of patients develop metastatic diseases and have a poor clinical outcome. Immunotherapies are quickly becoming a need, and recent research has produced some amazing achievements in this area. In the current investigation, an attempt was made to evaluate the prognostic usefulness of KDELR3 in UM, particularly its connection with tumor-infiltrating lymphocytes (TILs). The expression patterns of mRNAs and related clinical data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…There is a correlation between the gene KDELR3 and an increase in C-reactive protein. 23 In cSCC, there is a low level of expression of both ECM1 and WIPI1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a correlation between the gene KDELR3 and an increase in C-reactive protein. 23 In cSCC, there is a low level of expression of both ECM1 and WIPI1.…”
Section: Discussionmentioning
confidence: 99%
“…There is a correlation between the gene KDELR3 and an increase in C‐reactive protein. 23 In cSCC, there is a low level of expression of both ECM1 and WIPI1. ECM1 is responsible for regulating not just the development of the epidermis but also angiogenesis, the binding of cutaneous collagen and glycoproteins, and the process.…”
Section: Discussionmentioning
confidence: 99%
“…Other UM histopathologic features, such as tumor-infiltrating lymphocytes (TILs) and vascular patterns, have been classically correlated with the prognosis of UM. Although TILs are less frequently found in UM than in CM, two patterns of lymphocytic infiltration have been described: patchy or diffuse [57][58][59][60][61]. High levels of TILs have been correlated with poor prognosis and chromosome 3 loss in UM patients, while it has been widely accepted that they are predictive of a better outcome in other malignancies such as breast carcinoma, CM, and non-small cell lung cancer.…”
Section: Histopathological Features Of Ummentioning
confidence: 99%
“…For example, a microarray study demonstrated that KDELR3 is a biomarker of atherosclerosis (AS) onset 14 . In uveal melanoma (UM), KDELR3 is associated with prognosis, immune infiltration and chemoresistance 15 . The roles of KDELR3 in PAAD have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“… 14 In uveal melanoma (UM), KDELR3 is associated with prognosis, immune infiltration and chemoresistance. 15 The roles of KDELR3 in PAAD have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%